Groteska jako estetyczna odpowiedź na postulat dążenia do realności – uwagi o twórczości Karola Irzykowskiego (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The article reflects on the significance of the grotesque for the literary work of Karol Irzykowski. Through an analysis of three novellas – Wróg i nieprzyjaciel, Małżeństwo Maran and Metamorfozy Mojskiego, the author aims to indicate the mechanisms producing the grotesque effect in the text and to pose a question about the significance of its aesthetic shaping. According to the findings made in the text, the grotesque is a tool for distancing oneself from conventional ways of seeing reality, making it possible to get closer to the truth about it, to see its true image.